Metabolic reprogramming in glioblastoma: the influence of cancer metabolism on epigenetics and unanswered questions - Agnihotri, Sameer (Neuro Oncol, 2016)
A defining hallmark of glioblastoma is altered tumor metabolism. The metabolic shift towards aerobic glycolysis with reprogramming of mitochondrial oxidative phosphorylation, regardless of oxygen availability, is a phenomenon known as the Warburg effect. In addition to the Warburg effect, glioblastoma tumor cells also utilize the tricarboxylic acid cycle/oxidative phosphorylation in a different capacity than normal tissue. Altered metabolic enzymes and their metabolites are oncogenic and not simply a product of tumor proliferation. Here we highlight the advantages of why tumor cells, including glioblastoma cells, require metabolic reprogramming and how tumor metabolism can converge on tumor epigenetics and unanswered questions in the field.